PENGARUH KEPEMIMPINAN, PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASITERHADAP KINERJA KARYAWAN PT METRO BATAVIA - Fitria, Fitria (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2014)
This research is descriptive and associative. The population in this study are all employees of PT Metro Batavia 463 people. Engineering sample withdrawal is Proportional Random Sampling sample as many as 83 people. Analysis engineering is the analysis of descriptive data, classic assumption test: a test of its homogeneity and Normality Test, model test, path analysis, and hypothesis test by using Test t.The results showed that (1) there is a significant positive influence from the career development leadership, (2) there is a significant positive influence of leadership and organizational commitment to career development, (3) there is a significant positive influence of leadership, career development and organizational commitment to employee performance. The best lines from the results of this research are the indirect path, career development leadership through influence on performance of employees